Michigan Network of Libraries for the Blind and Physically Handicapped. 1993 Revised Standards for Subregional Libraries - Michigan Library, Lansing; Michigan Library, Lansing ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1993)
In November 1991, the State Librarian (Michigan) established a committee to review and revise the standards of service for the blind and physically handicapped. These revised standards define the general responsibilities of Michigan subregional libraries to their regional libraries and their borrowers. Responsibilities cover basic services such as the provision of informational and recreational books and magazines in special format along with the necessary audio playback equipment, accessories, and materials. Regional libraries are directed to conduct annual assessments to determine if the minimum standards are being met. General responsibilities of the state library to the network of libraries for the blind and physically handicapped concern funding, reporting procedures, liaison, collections, and marketing. The regional libraries have similar responsibilities to subregional libraries, which, in turn, have standards that assure uniform quality services to users. These encompass: (1) compiling statistical (readership, circulation, and machine inventories) and evaluative (assessment of subregional libraries' services) reports; (2) serving as liaison between the National Library Service for the Blind and Physically Handicapped (NLS), multistate centers, and subregional libraries, and providing consultant, technical, and reference assistance to subregional library staff; (3) lending, maintaining, and repairing disc and cassette machines and accessories; (4) providing support related to library collections, including maintaining a complete NLS (disc and cassette) collection as backup; (5) providing marketing services; (6) providing telephone access to patrons; and (7) coordinating volunteer efforts. Nine appendixes describe applicable statutes, list libraries, and define policies. (SLD)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Audio Equipment; Audiotape Recordings; Blindness; Braille; Financial Support; Guidelines; Library Administration; Library Circulation; Library Personnel; Library Services; Networks; Physical Disabilities; Policy; Program Evaluation; Special Libraries; Standard Setting; Standards; State Libraries; State Programs; Michigan; Guides, Non-Classroom.